An Empirical Model of Radiation Belt Electron Pitch Angle Distributions Based On Van Allen Probes Measurements. Issue 5 (6th May 2018) - Zhao, H.; Friedel, R. H. W.; Chen, Y.; Reeves, G. D.; Baker, D. N.; Li, X.; Jaynes, A. N.; Kanekal, S. G.; Claudepierre, S. G.; Fennell, J. F.; Blake, J. B.; Spence, H. E.
Abstract: Based on over 4 years of Van Allen Probes measurements, an empirical model of radiation belt electron equatorial pitch angle distribution (PAD) is constructed. The model, developed by fitting electron PADs with Legendre polynomials, provides the statistical PADs as a function of L‐shell ( L  = 1–6), magnetic local time, electron energy (~30 keV to 5.2 MeV), and geomagnetic activity (represented by the Dst index) and is also the first empirical PAD model in the inner belt and slot region. For megaelectron volt electrons, model results show more significant day‐night PAD asymmetry of electrons with higher energies and during disturbed times, which is caused by geomagnetic field configuration and flux radial gradient changes. Steeper PADs with higher fluxes around 90° pitch angle and lower fluxes at lower pitch angles for higher‐energy electrons and during active times are also present, which could be due to electromagnetic ion cyclotron wave scattering. For hundreds of kiloelectron volt electrons, cap PADs are generally present in the slot region during quiet times and their energy‐dependent features are consistent with hiss wave scattering, while during active times, cap PADs are less significant especially at outer part of slot region, which could be due to the complex energizing and transport processes. The 90°‐minimum PADs are persistently present in the inner belt and appear in the slot region during active times, and minima at 90° pitch angle are more significant for electrons with higher energies, which could be a critical evidence in identifying the underlying physical processes responsible for the formation of 90°‐minimum PADs. Key Points: Megaelectron volt electrons have steeper pitch angle distributions (PAD) during active times and for higher‐energy electrons, suggesting EMIC wave scattering Cap PADs are generally present in the slot region during quiet times with energy‐dependent features consistent with hiss wave scattering The 90°‐minimum PADs are persistently present in the inner belt, with more significant minima at 90° PA for electrons with higher energies